Determination of quarantine period in African catfish (Clarias gariepinus) fed with pig (Sus sp.) offal to assure compliance with halal standards - Wan Norhana, M.; Dykes, Gary; Padilah, B.; Ahmad Hazizi, A.; Masazurah, A. (2012)
Pig (Sus sp.) and pig by-products are considered as najasa (impurities) in Islam and forbidden in Muslim consumer products. Animals fed on najasa are categorised as al-jallālah (contaminated animals) which are allowed to be consumed as long as they have been quarantined for a certain period of time. During this quarantine period the animals will have undergone a natural purification process or istihālah. African catfish (Clarias gariepinus) are commonly consumed in Malaysia and may be fed on najasa. This study was carried out to estimate the istihālah period for catfish after feeding with pig offal, based on the absence of pig DNA in catfish gut and to suggest the quarantine period in catfish fed with pig offal. The results indicated that the maximum istihālah period could reach 36 h in the stomach, 6 h in the midgut and less than 2 h in the hindgut although in many cases shorter periods were observed. Based on these results it is estimated that the minimum quarantine period for catfish fed with pig offal is 1.5 days.